Otonomi Daerah - Lalu Sabardi (Jatiswara, 2012)
Research on the Legal Protection of the Coastal Zone, Coral Reef Protection Studies in Central Lombok regency was conducted on the basis of problems in local government's efforts for the maintenance terubu reefs in Central Lombok regency and about the institutional functions of the law enforcement community. The approach used in this study is empirical juridical approach, because the problem will be sought in the realm of social responsibilities, the law as part of social life. The data obtained in the analysis with qualitative analysis. The results of this fieldwork is setting on Coastal, Marine and Coral Reef, a nationally regulated by the sectoral rules, so that its management is also carried out sectorally, Coastal Management Authority, and the Coral Sea, has become a local government authority. However, in Central Lombok regency protection is not implemented as well as arrangements regarding the management of coastal, marine and coral reef communities and institutions have not shown concern for the protection of coastal, marine and coral reefs. The implications of this state that all the activities legalized by the law, because each instasi implement the program on their own rules, the consequences of coastal and marine activities be coordinated and not cause damage. On the basis of these two suggestions of this study is the Central Lombok regency administration must publish rules Coastal, Marine and Coral Reef to provide protection to the natural potential to be used for the maximum benefit of the people as it also should set up institutions that function is to coordinate the management and monitoring of coastal, marine and coral reefs to reduce damage caused by the construction of a sectoral nature.